Blockchain technology forecasting by patent analytics and text mining - Seyed Mojtaba Hosseini Bamakan (Elsevier, 2021)
Information technologies (ITs) have been playing an important role in improving our society, and the fast evolution of ITs creates a competitive environment not only for companies but also for regions. Hence, recognizing the future trend of technologies can be effective in decision-making with regard to technology selection and investment. Blockchain technology with its vast and impressive applications has received considerable attention from researchers, investors, and public agencies. The purpose of this research is to investigate blockchain technology to explore its trends according to their classification by use of the World Intellectual Property Organization (WIPO) database. Furthermore, we particularly evaluate the registered patents in the world's most well-known patent databases such as the USA patent database. We drew the current technology trends in blockchain patents by applying the text mining and clustering approach. The results represent that the registered patents in the USA patent database have been achieved in the growth phase. That means, attention to the blockchain is rising nowadays and most patents focused the cryptocurrencies and their applications in finance. However, blockchain technology is in the emergence phase and is evolving by researchers and inventors.